2020
DOI: 10.1017/s0272263119000767
|View full text |Cite
|
Sign up to set email alerts
|

Oral Language Profiles of English Second Language Learners in Adolescence

Abstract: It is often claimed that child English L2 learners take up to seven years to attain English skills commensurate with those of monolingual peers; however, existing research is insufficient to know if this claim is valid for oral language abilities in particular. This study examined the lexical and morphological abilities of English L2 learners and their monolingual peers (ages 12–15; N = 227) in Canadian middle schools to determine the timeline for convergence with monolinguals, and what factors predict individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Thus, whilst they are improving, they are not doing so at a rate that would indicate that they will at any time be able to close the gap on their nonimmigrant cohort. This result is in line with both broader quantitative studies on students' academic progression on standardized tests (Collier & Thomas, 2017;Cummins, 1979;Genesee, 1987) and with more recent studies on specific populations (Farnia & Geva, 2013;Levin & Shohamy, 2008;Paradis & Jia, 2017;Soto-Corominas et al, 2020). Reasons for this plateau in comparison to nonimmigrant students can only be guessed at; however, it is safe to assume that the dearth of continued German language support both within and outside of mainstream classrooms is not aiding the acquisition of the language.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Thus, whilst they are improving, they are not doing so at a rate that would indicate that they will at any time be able to close the gap on their nonimmigrant cohort. This result is in line with both broader quantitative studies on students' academic progression on standardized tests (Collier & Thomas, 2017;Cummins, 1979;Genesee, 1987) and with more recent studies on specific populations (Farnia & Geva, 2013;Levin & Shohamy, 2008;Paradis & Jia, 2017;Soto-Corominas et al, 2020). Reasons for this plateau in comparison to nonimmigrant students can only be guessed at; however, it is safe to assume that the dearth of continued German language support both within and outside of mainstream classrooms is not aiding the acquisition of the language.…”
Section: Discussionsupporting
confidence: 75%
“…This makes general statements about their academic progression difficult. Relevant for their success may be factors such as age at time of immigration (Clark-Gareca et al, 2019), literacy experience in the family language (L1) (Bialystok, 2007;Knapp, 1999), amount of time spent in the new school system (Soto-Corominas et al, 2020), participation in L1 classes after immigration (González, 1986), type of integration model (Collier & Thomas, 2017;Umansky & Reardon, 2014), relatedness of the L1 to the new L2 (Schepens et al, 2020), use of known L2s in learning the new language (Marx, 2005), and possibly refugee status (Woods, 2009), amongst others.…”
Section: Linguistic and Academic Progression Of Immigrant Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…So, some bilingual children’s vocabulary abilities were similar or above average when benchmarked to their monolingual peers, while others were more than 2 standard deviations below the normal range for monolinguals. Soto-Corominas, Paradis, Rusk, Marinova-Todd, and Zhang (2020a) found much wider within-group variation in performance on English language tasks for bilingual versus monolingual middle school students, even for bilinguals who had received all of their education in the L2 (more than 7 years). As early as the toddler years, simultaneous bilinguals show more within-group variation in lexical and grammatical development than their monolingual peers on the same language measures (Hoff, Core, Place, Rumiche, Señor & Parra, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…While sentence repetition tasks may be more efficient in assessment, naturalistic production tasks have the advantage in that they can reveal possible targets for intervention with children diagnosed with DLD. Complex syntax is a component of CALP-cognitive academic language proficiency (Cummins, 2000;NASEM, 2017) and bilingual students can take up to 5-7 years in school to converge with their monolingual classmates for CALP (Soto-Corominas et al, 2020). As mentioned earlier, Fletcher and Frizelle (2017) suggested that difficulties in the acquisition of complex syntax could underlie the weaker academic outcomes of monolingual children with DLD (Fletcher and Frizelle, 2017).…”
Section: Clinical Implications and Limitationsmentioning
confidence: 99%